Treatment with onion bulb extract both prevents and reverses allergic inflammation in a murine model of asthma - Ahmed Z. El-Hashim; Maitham A. Khajah; Khaled Y. Orabi; Sowmya Balakrishnan; Hanan G. Sary; Ahmad M. Barakat (Taylor & Francis Group, 2024)
AbstractContext Asthma presents a global health challenge. The main pharmacotherapy is synthetic chemicals and biological-based drugs that are costly, and have significant side effects. In contrast, use of natural products, such as onion (Allium cepa L., Amaryllidaceae) in the treatment of airway diseases has increased world-wide because of their perceived efficacy and little safety concerns. However, their pharmacological actions remain largely uncharacterized.Objective We investigated whether onion bulb extract (OBE) can (1) reverse established asthma phenotype (therapeutic treatment) and/or (2) prevent the development of the asthma phenotype, if given before the immunization process (preventative treatment).Materials and methods Six groups of male Balb/c mice were established for the therapeutic (21 days) and five groups for the preventative (19 days) treatment protocols; including PBS and house dust mite (HDM)-challenged mice treated with vehicle or OBE (30, 60, and 100 mg/kg/i.p.). Airways inflammation was determined using cytology, histology, immunofluorescence, Western blot, and serum IgE.Results Therapeutic (60 mg/kg/i.p.) and preventative (100 mg/kg/i.p.) OBE treatment resulted in down-regulation of HDM-induced airway cellular influx, histopathological changes and the increase in expression of pro-inflammatory signaling pathway EGFR, ERK1/2, AKT, pro-inflammatory cytokines and serum IgE.Discussion and Conclusion Our data show that OBE is an effective anti-inflammatory agent with both therapeutic and preventative anti-asthma effects. These findings imply that onion/OBE may be used as an adjunct therapeutic agent in established asthma and/or to prevent development of allergic asthma. However, further studies to identify the active constituents, and demonstrate proof-of-concept in humans are needed.